2004
DOI: 10.1073/pnas.0402180101
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the classical complement pathway: Lamprey orthologue of mammalian C1q acts as a lectin

Abstract: The lectin complement pathway in innate immunity is closely related to the classical complement pathway in adaptive immunity, with respect to the structures and functions of their components. Both pathways are initiated by complexes consisting of collagenous proteins and serine proteases of the mannose-binding lectin (MBL)-associated serine protease (MASP)͞C1r͞C1s family. It has been speculated that the classical pathway emerged after the lectin pathway, and that the activation mechanism of the latter was part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 33 publications
0
93
0
Order By: Relevance
“…Mice deficient in C1q, MBL, or secreted IgM have impaired control of inflammatory responses and, in some cases, autoimmune predisposition (36)(37)(38)(39). The regulatory inhibitory signaling properties of the anti-AC IgM were shown to be dependent on the presence of C1q or MBL, two soluble macromolecules of the innate immune system that share a common primordial genetic ancestor (40). When deposited on the surface of an AC, these represent "eat me" signals that enhance apoptotic clearance (41); however, we found that by themselves these recognition molecules demonstrated no significant activity in our assays.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in C1q, MBL, or secreted IgM have impaired control of inflammatory responses and, in some cases, autoimmune predisposition (36)(37)(38)(39). The regulatory inhibitory signaling properties of the anti-AC IgM were shown to be dependent on the presence of C1q or MBL, two soluble macromolecules of the innate immune system that share a common primordial genetic ancestor (40). When deposited on the surface of an AC, these represent "eat me" signals that enhance apoptotic clearance (41); however, we found that by themselves these recognition molecules demonstrated no significant activity in our assays.…”
Section: Discussionmentioning
confidence: 99%
“…For that property they have potential antimicrobial activity in the skin mucus. Lectins interact with pathogenic surface structures that result in opsonisation, enhance phagocytic activity [194], or activation of the complement pathway [195]. Furthermore, agglutinins in fishes are reported to prevent polyspermy [196] and assist in wound healing [60].…”
Section: Lectinsmentioning
confidence: 99%
“…Peptide Institute) as previously described (21). The activity was expressed as fluorescence intensity determined at 380 nm for excitation and 460 nm for emission.…”
Section: Treatment Of Rc1s With Trypsin and Its Characterizationmentioning
confidence: 99%